A Comment on Dr Klein's Interpretation of Leontief's System - Morishima, Michio (Review of Economic Studies, 1956)
Journal Article A Comment on Dr Klein's Interpretation of Leontief's System Get access Michio Morishima Michio Morishima Osaka Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 24, Issue 1, 1956, Pages 65–68, https://doi.org/10.2307/2296238 Published: 01 July 1956